Understanding the Patterns of Processed Seafood Exports from Sri Lanka: Application of the Gravity Model to Quantify the Determinants (Quest Journal of Management and Social Sciences, 2020)
Background: Grabbing the emerging opportunities, from the escalated global demand for processed seafood due to the modern lifestyle induced changes in the food consumption pattern of the households, could be a great advantage for Sri Lanka to increase its international trade activity. This could also help Sri Lanka earn more revenues by adding value through the processing of the raw fish and through that eliminating high postharvest loss during the peak seasons.Objective: This research intends to study the patterns of global and Sri Lankan trade in the seafood sector and identifies the determinants in terms of their impacts on the processed seafood export.Methods: The Gravity Model was run with the secondary data collected from UNCOMTRADE. The panel data include seafood export data of Sri Lanka from 2001 to 2014 with 107 countries and 144 products.Results: However, only one % of the Sri Lankan processed seafood adds value to the ultra-processed level, so it cannot reach the maximum potentials in job creation and profitability. This study has found that the elasticity values of tariff and non-tariff measures (NTMs) are higher for the processed seafood than the unprocessed seafood. This way, the processed seafood becomes more vulnerable to changes in tariff and NTMs than the unprocessed seafood.Conclusions: The conversion of unprocessed seafood into processed seafood can improve the export revenue for Sri Lanka but these conversions are increasing the vulnerability of seafood exports due to the stringent market barriers.